Design of a cable-driven hyper-redundant robot with experimental validation. (24th October 2017) - Tang, Lei; Wang, Jungang; Zheng, Yang; Gu, Guoying; Zhu, Limin; Zhu, Xiangyang
This article presents a test bed for comprehensive study of a cable-driven hyper-redundant robot in terms of mechanical design, kinematics analysis, and experimental verification. To design the hyper-redundant robot, the multiple section structure is used. Each section consists of two rotational joints, a link mechanism, and three cables. In this sense, two degrees of freedom are achieved. For kinematics analysis between the actuator space and joint space, each section of the development is treated as three spherical–prismatic–spherical chains and a universal joint chain (3-SPS-U), which results in a four-chain parallel mechanism model. In order to obtain the forward kinematics from the joint space to task space directly and easily, the coordinate frames are established by the geometrical rules rather than the traditional Denavit–Hartenburg (D-H) rules. To solve the problem of inverse kinematics analysis, we utilize the product of exponentials approach. Finally, a prototype of 24-degrees of freedom hyper-redundant robot with 12 sections and 36 cables is fabricated and an experiment platform is built for real-time control of the robot. Different experiments in terms of trajectories tracking test, positioning accuracy test, and payload test are conducted for the validation of both mechanical design and model development. Experiment results demonstrate that the presented hyper-redundant robot has fine position accuracy, flexibility with mean position error less than 2%, and good load capacity.